Three new species of Miltochrista Hübner from India, Myanmar, Nepal and China (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Singh, Navneet; Černý, Karel; Kirti, Jagbir Singh; Datta, Harvinder Singh (Zootaxa, 2022)
Three new species of the genus Miltochrista Hübner, [1819] are described: M. idiomorfa sp. n. (India, Nepal, N Myanmar and SW China), M. dankana sp. n. (India and north-western Myanmar) and M. etalina sp. n. (Northeast India). Miltochrista straminea Walker, 1856, stat. rev. is restored to species level. The lectotype for Miltochrista straminea is designated. Adults, male and female genitalia of the new and similar species are illustrated.